Reproducción de Polymita muscarum y Polymita venusta (Stylommatophora: Helminthoglyptidae) - Bidart, Liana (1998)
The reproduction of the terrestrial snails Polymita muscarum and Polymita venusta was studied under laborarory and natural living conditions. Eight natural populations were sampled in Holguín Province, Cuba, from September 1985 through May 1990. In the laboratory, 46 P. muscarum and 25 P. venusta were kept in 32.3 cm x 22.8 cm x 30.7 cm terraria and fed fungi-infested branches. The reproduction season was July-December in the laboratory and July-January in nature. Times between copulation and oviposition were 18 days for P. muscarum and 20 days for P. venusta and for incubation, 8 days. Mean number of eggs per nes!: P. muscarum 84. 12, P. venusta 142.2; natality rates: 52.65 % and 19.9 % respective1y.